Answer :

To Find: Differentiation


NOTE : When 2 functions are in the product then we used product rule i.e


Formula used: (yn) = nyn - 1


Let us take y= = (x2 - x + 3) - 3


So, by using the above formula, we have


(x2 - x + 3) - 3 = - 3(x2 - x + 3) - 4(2x - 1) = - 3 (2x - 1)


Differentiation of y = (x2 - x + 3) - 3 is


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

If f(x) = x sin xRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

DifferentiaRS Aggarwal - Mathematics